DETERMINATION OF THE VOCATIONAL TAXONOMY HIERARCHY FOR HIGHER VOCATIONAL SCHOOL - Sadrina, Sadrina; Lebay Long, Norhazizi; Mustapha, Ramlee; Yuana, Yuyun (Universitas Islam Negeri Alauddin Makassar, 2021)
Taxonomy can be defined as the naming or classification of an idea or name, according to one discipline. There is a lack of regulation in the concept of vocational education. Vocational education (SMK) cannot fully use Bloom's Taxonomy. Vocational Taxonomy is centered on psychomotor theory which emphasizes aspects of physical movement. However, the purpose of this research is to determine the appropriate Vocational Taxonomy hierarchical structure for SMKN 1 Jeunib. The design of this research is qualitative research which using interview method to assess the perception of the Vocational teacher in terms of determination the Vocational Taxonomy. The sample chosen was SMKN 1 Jeunib, Bireun, Aceh, which selected 54 teachers from all departments. The result presented that the teachers believed Vocational Taxonomy is important for SMK learning and teaching. In addition, the taxonomic function is very important and assisting in teaching and learning, aiding the curriculum preparation and contributing the practical activities. Then also, the taxonomy function is important in measurement and assessment of psychomotor activities. So, the Taxonomy was recommended to related parties (SMK, Polytechnic, Vocational College, or training Institution). The research also stated that there was a need for a link between cognitive and psychomotor aspects. Finally, the students not only mastered the aspects of knowledge but also proficiency.